RANCANG BANGUN APLIKASI INFORMASI TEMPAT OLAHRAGA DIKOTA BATAM BERBASIS ANDROID MENGGUNAKAN METODE LOCATION BASED SERVICE - Emanuel Antonius Suban Weruin; Hutabri, Elbert (Computer Science and Industrial Engineering, 2025)
Sport is an activity that trains the human body's endurance, where the body is trained more than usual, usually the body often becomes weak if you don't exercise often because the body's endurance decreases, exercise can have a good effect on the body, so the effect of exercise is itself can have a good impact on our bodies. Batam City is a city Industry, Where one of the cities that has the majority of the city's population is workers from various types of work, which require maximum endurance and require more extra energy, In the modern era filled with technology, the need for fast and easily accessible information about sports venues has become increasingly important. Batam City, as a rapidly developing economic and tourism center in Indonesia, is also experiencing an increase in interest and talent in sports activities, therefore, the development of a sports venue information system in Batam City is based on Android with method Location Based Service has become a necessity.